Acceptance sampling plans from a truncated life test based on the power Lomax distribution with application to manufacturing - Amjad D. Al-Nasser; Muhammad Ahsan Ul Haq (Statistics in Transition New Series, 2021)
In this research, a new acceptance sampling plan for a truncated life test is presented, assuming that the quality characteristic follows the power Lomax distribution. The operating characteristic function values are calculated for the proposed sampling plan, jointly with the optimal sample size and the producer's risk for a selection of distribution parameters. Furthermore, a comparative study with other sampling plans is introduced to demonstrate the advantages of the proposed plan. Finally, a real-life example illustrating the applicability of the proposed sampling plan in a manufacturing company is discussed.
Keywords: 519; acceptance sampling plan; operating characteristic; power Lomax distribution; industry; data analysis